The Interplay Between Housing Stability and Child Separation: Implications for Practice and Policy. Issue 1 (5th July 2017) - Rog, Debra J.; Henderson, Kathryn A.; Lunn, Laurel M.; Greer, Andrew L.; Ellis, Mei Ling
Highlights: Housing plays an important role in fostering family stability and residential stability. Families in supportive housing are more likely to reunite with children than families in shelter. Families with child separations are less likely to be in their own housing following shelter entry. Abstract: Greater understanding of how residential stability affects child separation and reunification among homeless families can guide both child welfare and homeless policy and practice. This article draws upon two longitudinal studies examining services and housing for homeless families and their relationship to family and housing stability. Both studies were conducted in the same state at roughly the same time with similar instruments. The first study, examining families' experiences and outcomes following entry into the homeless service system in three counties in Washington State, found that at 18 months following shelter entry, families that are intact with their children were significantly more likely to be housed in their own housing (46%) than families that were separated from one or more of their children (31%). The second study, a quasiexperimental evaluation of a supportive housing program for homeless families with multiple housing barriers, found that the rates of reunification for Child Protective Services (CPS)‐involved families receiving supportive housing was comparable to that for families entering public housing without services, but significantly higher than the rate of reunification for families entering shelter. Taken together, the findings from both studies contribute to the evidence underscoring the importance of housing assistance to homeless families involved in the child welfare system.